Effects of the Ripening Time of Porcelain Banana (Musa spp. Abb cv. Pisang awak) on the total Polyphenol Contents and Bioactivities - Ha, Hue Thi; Mai, Son The; Mai, Nhi Tuyet; Phan, Dao Thi Anh (Journal of Technical Education Science, 2023)
To investigate the influence of the banana ripening stage on the change in the content of bioactive components and their bioactivities, ripening stages of porcelain banana peels were screened for the total phenolic content (TPC) and antioxidant activities using three methods, including DPPH scavenging assay, ferric reducing/antioxidant power (FRAP) assay, and inhibition of polyphenol oxidase activity (PPO assay). The Pearson correlation analysis of antioxidant parameters of banana peel extracts for each ripening stages with TPC data showed that the TPC values in the sample extracts were strongly negatively correlated with the IC50 values of the DPPH assay (r = -0.905). They positively correlated with the Fe3+ reduction capacity of Fe2+ (r = 0.723) and the ability to inhibit PPO enzyme at a concentration extract of 100 µg/mL (r = 0.786). During the ripening of bananas, the TPC at stage 1 (M1, light green, 228 mg GAE/100 g DW) was highest, and decreased to a minimum at stage 4 (M4, yellow color, accounts for 50% to 85% of the total banana peel surface area), and increase in stage 6 (M6, yellow color and appearance of black points, 199.9 mg GAE/100 g DW). The banana peel extract in stage 6 showed intense activities, having the highest extraction yield (15.18%) and was analyzed chemical constituents by HPLC-MS, which showed that it contains valuable group compounds such as phenolic acids, flavonols, flavan-3-ols, catecholamines, lignans, and antibacterial compounds. This shows the potential of using banana peels to prepare polyphenol extracts containing high antioxidant activities, enhancing the use value of bananas.